A remarkable new genus of carnivorous, sessile bivalves (Mollusca: Anomalodesmata: Poromyidae) with descriptions of two new species - Leal, José H. (Zootaxa, 2008)
Dilemma, a new genus of sessile septibranch bivalves is described. The new taxon encompasses at least three species, of which two are new: D. frumarkernorum new species, from off the Florida Keys, D. spectralis new species, from off Vanuatu, and “Corculum” inexpectatum Crozier, 1966, from off the Three Kings Islands, New Zealand, known only from its shell. The absence of ctenidia and presence of a septum, size and arrangement of siphons and siphonal tentacles, extensive fusion of the mantle margins allocate the new genus within the septibranch bivalves. A siphonal area with 15 tentacles, a large and eversible incurrent siphon, ostial apertures in the septum, and a hermaphroditic reproductive system suggest inclusion in the Poromyidae. The presence of three paired groups of septal ostia in the new genus is a feature shared with poromyids in the genus Cetoconcha. Unusual symmetry and form constitute the most striking features of the new genus. There is a strong anteroposterior compression and lateral expansion associated with ca. 30º rotation of the largest dimension (height) in relation to the anteroposterior axis. The shell hinge includes a single tooth and socket on each valve, and an external, but deeply sunken ligament. The two new species, mutually distinguishable by shell and anatomical characters, are known from live-collected specimens found adhering to rocks by means of robust byssus, which indicates attachment for life. The presence of ostracod remains in the digestive tract of one specimen of one of the new species and of a cirolanid isopod in the stomach of the holotype of the second new species are evidence of predation. Although predation by infaunal and free-living bivalves is known to occur throughout the Anomalodesmata, in particular within the septibranchs, discovery of the new genus reveals an unusual instance of predation by sessile, permanently attached mollusks.